Cardiovascular diseases risk factors among adult diabetic patients in eastern Ethiopia. (September 2019) - Abdosh, Tekabe; Weldegebreal, Fitsum; Teklemariam, Zelalem; Mitiku, Habtamu
Objective: The aim of this study was to determine the magnitude of cardiovascular disease risk factors among adult diabetic patients at Hiwot Fana Specialized University Hospital and Jugal Hospital, eastern Ethiopia. Methods: An institutional based cross sectional study was conducted on a total of 416 study participants (age ≥18 years) from February to March 2017. Data were collected using: structured questionnaires, measurements of weight, height, and blood pressure, and laboratory examination of blood lipids (total cholesterol, triglycerides, low-density lipoprotein, and high-density lipoprotein cholesterol) and fasting blood glucose. Data were analyzed using SPSS version 16.0 software packages. The association of cardiovascular disease risk factors with diabetes type, age, and sex was assessed by chi-square test. Result: The mean age of study participants was 52 years and 44% were male. Dyslipidemia (90.6%), physical inactivity (76%), and hypertension (62.7%) were the most common cardiovascular disease risks factors identified among diabetic patients. It was also observed that 68.5% of the study participants had uncontrolled blood glucose level. Hypertension was significant in patients over 65 compared to those ≤65 years of age (p < 0.023). Females were considered to be significantly physically inactive compared to males (p < 0.001). Conclusion: Dyslipidemia is the most common risk factor of CVD in individuals with Types 1 and 2 diabetes mellitus. Identification and treatment of lipid abnormalities is very important. Controlling hypertension among older patients and lifestyle modification among female diabetic patients are also recommended.